Serum triglyceride level: a predictor of complications and outcomes in acute pancreatitis? - Anandaravi, B. N.; Kalavathi, L. (International Surgery Journal, 2019)
Background: The aims and objectives were to analyse the influence of elevated triglyceride level in acute pancreatitis so the ability to predict the severity of acute pancreatitis can help identify the patients at increased risk of morbidity and mortality, therefore to make an early decision to triage these patients and treat accordingly. Methods: An observational study was undertaken over a span of 6 months from January 2018 to June 2018 in K.R Hospital, Mysore, Karnataka, India. 50 Patients admitted with the diagnosis of acute pancreatitis, who had serum triglyceride levels measured within the first 24 hrs of admission, were divided into 2 groups. The study group consisted of patients with a triglyceride level ≥200 mg/dl (group 2) and the control group consisted of triglyceride level of ≤ 200 mg/dl (group 1). We collected the detailed history, data of laboratory values, incidence of complications like pleural effusion, acute kidney injury, pancreatic necrosis, shock, admission to ICU, length of total hospital stay and death. Results: A total of fifty patients were included in the study out of which 42 patients had triglycerides of less than 200 mg/dl and 8 patients had triglycerides of more than 200 mg/dl. There was no significant difference in the incidence of pleural effusion and shock but there was significant difference in the incidence of acute kidney injury, pancreatic necrosis and Intensive care unit stay between the two groups. Conclusions: A triglyceride level of more than 200 mg/dl on admission in acute pancreatitisis is an independent predictor of developing local and systemic complications, hospital stay, admission to ICU and death.